Progress in understanding Legg–Calvé–Perthes disease etiology from a molecular and cellular biology perspective - Zheng, Xinda; Dong, Zhuqing; Ding, Xiaofei; Huang, Qian; Tang, Shengping; Zhang, Yuchen; Li, Boxiang; Liao, Shijie (Frontiers in Physiology, 2025)
Legg–Calvé–Perthes disease (LCPD) is a hip disease caused by ischemia of the femoral epiphysis in children, which occurs in children aged 4–8 years (mean 6.5 years), with a male-to-female ratio of about 4:1. The disease has been reported for more than 100 years, but its etiology has not been elucidated. In recent years, a considerable amount of research has been carried out on the etiology of the disease, and the development of the disease is believed to involve a variety of molecular biological alterations, such as the COL2A1 mutation, which may be one of the causes of necrotic collapses of the epiphyseal cartilage matrix in LCPD. Tissue factor V Leiden mutation and insulin-like growth factor (IGF-1) abnormalities have also been reported in LCPD, but most theories need further confirmation. The in-depth study of LCPD cell biology has facilitated the suggestion regarding structural and/or functional abnormalities of microvascular endothelial cells in LCPD. This conjecture is supported by epidemiological and clinical evidence. Abnormal activation of osteoclasts, ischemic damage to epiphyseal cartilage, and activation of the bone marrow immune system all play important roles in the onset and progression of the disease. In this paper, we review the previous basic studies on LCPD and give an overview from the molecular biology and cell biology perspectives.